A novel P300-based brain-computer interface stimulus presentation paradigm: moving beyond rows and columns. - Townsend, G.; LaPallo, B. K.; Chadwick B. Boulay; Krusienski, D. J.; Frye, G. E.; Hauser, C. K.; Schwartz, N. E.; Theresa M Vaughan; Jonathan Wolpaw; Sellers, E. W. (Clinical neurophysiology : official journal of the International Federation of Clinical Neurophysiology, 2010)
OBJECTIVE: An electroencephalographic brain-computer interface (BCI) can provide a non-muscular means of communication for people with amyotrophic lateral sclerosis (ALS) or other neuromuscular disorders. We present a novel P300-based BCI stimulus presentation - the checkerboard paradigm (CBP). CBP performance is compared to that of the standard row/column paradigm (RCP) introduced by Farwell and Donchin (1988). METHODS: Using an 8x9 matrix of alphanumeric characters and keyboard commands, 18 participants used the CBP and RCP in counter-balanced fashion. With approximately 9-12 min of calibration data, we used a stepwise linear discriminant analysis for online classification of subsequent data. RESULTS: Mean online accuracy was significantly higher for the CBP, 92%, than for the RCP, 77%. Correcting for extra selections due to errors, mean bit rate was also significantly higher for the CBP, 23 bits/min, than for the RCP, 17 bits/min. Moreover, the two paradigms produced significantly different waveforms. Initial tests with three advanced ALS participants produced similar results. Furthermore, these individuals preferred the CBP to the RCP. CONCLUSIONS: These results suggest that the CBP is markedly superior to the RCP in performance and user acceptability. SIGNIFICANCE: The CBP has the potential to provide a substantially more effective BCI than the RCP. This is especially important for people with severe neuromuscular disabilities.
Keywords: brain-computer interface; brain-machine interface; EEG; event-related potential; P300; Rehabilitation